Warfare state : Britain, 1920 - 1970 - Edgerton, David 16.04.1959- (Cambridge Univ. Press, 2006)
'Warfare State' challenges the central theme of the existing histories of 20th century Britain, that the British state was a welfare state. It argues that it was also a warfare state, which supported a powerful armaments industry. The book is a substantial reinterpretation of the British state in the 20th century.